Kardiochirurgia dorosłych Long-term angiotensin converting enzyme inhibition and postoperative risk of atrial fibrillation following coronary artery bypass grafting - Szyndler, Krzysztof; Siondalski, Piotr; Pawlaczyk, Rafał; Jarmoszewicz, Krzysztof; Łaskawski, Grzegorz; Łoś, Andrzej; Jagielak, Dariusz; Rogowski, Jan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Background: Postoperative atrial fibrillation (PAF) occurs in up to 50% of patients and represents the most common complication after coronary artery bypass grafting (CABG). Recent studies demonstrated significant reduction of paroxysmal AF in patients with heart failure or left ventricle hypertrophy treated with angiotensin-converting enzyme inhibitors (ACEI). AIM of the study was to determine whether chronic ACEI therapy has an impact on the incidence of PAF after CABG. Materials and methods: The study was performed on 360 patients with coronary artery disease. 255 patients receiving ACEI and 105 patients without ACEI underwent isolated CABG. Results: Postoperative AF was observed in 20.4% of subjects of the ACEI group and 32.4% of controls (p=0.015). ACEI therapy was the only independent factor reducing the risk of PAF (OR 0.44; 95% CI 0.25-0.78; p <0.001). Relative risk reduction of PAF for ACEI therapy equals 37%. Conclusion: Long-term ACEI therapy significantly reduces PAF in patients after CABG.